2003
DOI: 10.1111/j.1365-2133.2003.05740.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the incidence of skin cancer and its risk factors in a Spanish Mediterranean population of kidney transplant recipients

Abstract: Our study confirms the high incidence of non-melanoma skin cancer among KTRs in a Mediterranean population with occupational sun exposure and the patient's age at the time of transplantation being the main risk factors. We believe that all organ transplant programs should provide educational information about protecting oneself from the sun as well as include follow-up visits by dermatologists in order to facilitate early diagnosis and treatment of skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
85
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 23 publications
17
85
1
2
Order By: Relevance
“…8 The incidence of posttransplant skin cancer varies from 2% to 68%. [9][10][11][12] In the present study, incidence of skin cancers was found to be 37.3% and compatible with the literature. Advanced patient age is a common risk factor for skin tumors in transplant recipients; patients aged 102…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…8 The incidence of posttransplant skin cancer varies from 2% to 68%. [9][10][11][12] In the present study, incidence of skin cancers was found to be 37.3% and compatible with the literature. Advanced patient age is a common risk factor for skin tumors in transplant recipients; patients aged 102…”
Section: Discussionsupporting
confidence: 78%
“…9,12,13 Similar to the literature, the mean age of our patients with skin cancers was 48.9 ± 12.2 years, and it is significantly higher than that of patients who developed other malignant tumors. The development of skin SCC was reported more frequently than BCC in kidney transplant recipients.…”
Section: Eda Yılmaz Akçay Et Al/experimental and Clinical Transplantasupporting
confidence: 74%
See 2 more Smart Citations
“…An incidence rate about 2.3-3.1% has been reported for organ-transplant related malignancies [8,9]. The most common malignancy observed in solid organ transplant recipients is non-melanoma skin cancer (NMSC) [10][11][12] and particularly in squamous cell carcinoma (relative risk 14-82) [13,14]. Many etiologic factors such as ultraviolet radiation, human papillomavirus infection, genetics and immunosuppressive therapy play an important role in the occurrence of post-transplant NMSC [15,16].…”
Section: Introductionmentioning
confidence: 99%